Rancangan Produk Rekreasi Wisata Memancing Sungai Bogowonto, Kabupaten Purworejo - Beta Budisetyorini; Deddy Adisudharma; Dicky Arsyul; Wisi Wulandari; Mega Fitriani Adiwarna Prawira (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2022)
The distribution of tourism potential in Purworejo Regency has been well mapped and must be supported by suitable approach, one of which is the development of river tourism. The actual river tourism activities that have been developed on the Bogowonto River are adventure tourism activities, namely white water rafting. However, the potential of river tourism on Bogowonto River is not only limited for rafting. The development of recreational fishing products on the Bogowonto River can be an opportunity for tourism development in Purworejo Regency. Recreational fishing regarded as a form of tourism activity in accordance with sustainable tourism (Hall, 2019; UNWTO, 2021). This can be seen from the pattern of recreational fishing that does not focus on the number of fish caught, the arrangement of the tools used, as well as the positive impact given to the community on the economic side. The study (Butler et al., 2020) shows that there is a positive contribution of fishing tourism to ecological preservation. From the business side, the Government of Indonesia has regulated fishing tourism businesses (Regulation of the Minister of Tourism of the Republic of Indonesia No. 19 of 2015 concerning Standards for Fishing Tourism Business, 2015), including business arrangements for providing places and facilities for fishing activities using special equipment and safety equipment including the provision of guide services. This study will identify and analyze recreational fishing tourism products based on packages, fishing equipment, fishing tour guides and supporting facilities in the Bogowonto River Area, Purworejo Regency. The long-term goal of this research is to contribute to the design of recreational fishing products for the development of tourist destinations in Purworejo Regency as a guide for stakeholders regarding the utilization of the Bogowonto River